LEGAL PROTECTION FOR PASSENGERS IN PUBLIC TRANSPORT ACCIDENT INSURANCE CLAIMS IN INDONESIA - Tunggati, Melki T.; Piyo, Sofyan (NOMOI Law Review, 2025)
Legal protection for passengers in public transportation accident insurance claims in Indonesia is an important aspect in guaranteeing the rights of accident victims. Although various regulations have regulated the obligation of transportation service providers to provide accident insurance, there are still various obstacles in its implementation, such as complicated claim procedures, low passenger awareness of their rights, and lack of supervision of transportation and insurance companies. This research uses a normative legal research method with a statutory approach and a case approach. The sources of legal materials consist of primary, secondary, and tertiary legal materials collected through literature study and analyzed qualitatively. The results show that although regulations such as Law Number 33 of 1964 and Law Number 8 of 1999 have provided a legal basis for passenger protection both preventively and repressively, there are still challenges in its implementation. The main obstacles include regulations and policies, complicated bureaucracy, lack of socialization of passenger rights, and weak law enforcement against negligent companies. Therefore, improvements in regulations, simplification of claim procedures, and increased supervision are needed to ensure passenger rights are effectively protected.